Ekstraksi Silika dari Fly Ash Pabrik Kelapa Sawit Menggunakan Variasi Pelarut Karbonat - Regna Tri Jayanti; Jerry; Miftahurrahmah (Jurnal Teknik Kimia USU, 2023)
The selection of a catalyst is imperative in extracting silica. Calcium is a heterogeneous base catalyst that is abundant in carbonate rocks. This study attempts to extract silica using an artificial carbonate solvent with variations of strong acid HCl (1 M, 3 M, 5 M), NaCl salt (1: 2, 1: 4) w/w ratio to distilled water, and H2O (1: 4) w/w ratio to carbonate. Characteristics of fly ash were analyzed using XRF and XRD to determine the elemental composition, crystal structure, and dominant constituent compounds. The solvent concentration and pH effect in extracting silica from fly ash is reviewed by setting the temperature parameter at 60 C, 120 minutes extraction time, and the ratio between fly ash and carbonate solvent 20 % w/v. The filtrate was verified using UV-Vis to determine the concentration of dissolved silica (SiO2) in the carbonate solvent. The examination results showed that the carbonate solvent with 3 M HCl was able to extract silica better than the other five solvents at 68.17 ppm.Â